Registration and its Impact on the Legal Protection of the Trademark: An Analytical Study of the Provisions of the Jordanian Trademark Law - Obeidat, Ibrahim Mohammad (Dirasat: Shari'a and Law Sciences, 2021)
The Jordanian legislator approved on the legal protection for the trademark as an intellectual property right. This protection comes as a result of the provisions and rules which are provided by the Trademark Law that linked this protection to the registration of the trademark. This study focuses on explaining the legal aspects of the implications of trademark registration by clarifying the rights that the Trademark Law has given to its owner. To demonstrate the importance of registration, it is necessary to show the rights of the unregistered trademark owner to find out the reality of this legislative approach by clarifying the justifications and the reasons behind it, by following the analytical method. The study followed a methodology to indicate the rules related to trademark protection based on the rules of the texts of the trademark law contained in the Jordanian legislature. The study concluded that the registration originates the right to the trademark, and results in civil and penal protection of it. On the other hand, this law did not approve this protection for an unregistered trademark which is alternatively guaranteed by Unfair Competition Law and the Trade Secrets Law. Based on that, a recommendation was made to the legislator to amend some provisions of the trademark law in line with these results.